THE EFFECT OF EXERCISE CONSULTATION PROGRAM ON EXERCISE BEHAVIORAL CHANGES IN PATIENTS OF TYPE 2 DM WITH OVERWEIGHT : TRANSTHEORETICAL MODEL APPROACH - Rinco Siregar; Karnirius Harefa; Eva Kartika Hasibuan (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
The purpose of this quasi- experimental study was to determine the effect of exercise consultation program based on Transtheoretical Model (TTM) approach on exercise behavioral change, blood glucose and body mass index (BMI) in patients of T2DM with overweight. The two comparison groups, quasi-experimental study were purposively designed for pre-test/post-test procedures; 61 patients of T2DM allocated into the experimental (31 patients) and the control (30 patients) groups. While the experimental group received the exercise consultation for 12 weeks, the control group received routine care. Comparative assessments on differences in exercise behavioral changes, blood glucose and BMI were examined both within and between groups using Chi-Square test and t-test. After receiving exercise consultation program, 54.8 % of participants of the experimental group had progressed to the action stage of change of TTM, while the majority of the participants in the control group (43.3%) remained in the same stages of TTM, and only 3.3 % of the participants had progressed to the maintenance stage. This proportion of exercise behavior change between the groups was significantly statistical different (Chi-Square = 000, p <0.05). Blood glucose significantly decreased in the experimental group (p < .05), but there was no significant difference in the control group.No significant difference of mean scores of BMI of participants between the experimental group and the control group post-intervention of exercise consultation program (p > .05). In conclusion, the exercise consultation program could promote the exercise behaviors. This also improves health outcome on blood glucose among patients of T2DM who.Keywords: transtheoretical model; physical exercise; type 2 diabetes